In-Depth Study of Transmembrane Mucins in Association with Intestinal Barrier Dysfunction During the Course of T Cell Transfer and DSS-Induced Colitis. (31st January 2020) - Breugelmans, Tom; Van Spaendonk, Hanne; De Man, Joris G; De Schepper, Heiko U; Jauregui-Amezaga, Aranzazu; Macken, Elisabeth; Lindén, Sara K; Pintelon, Isabel; Timmermans, Jean-Pierre; De Winter, Benedicte Y; Smet, Annemieke
Abstract: Background and Aims: There is evidence for a disturbed intestinal barrier function in inflammatory bowel diseases [IBD] but the underlying mechanisms are unclear. Because mucins represent the major components of the mucus barrier and disturbed mucin expression is reported in the colon of IBD patients, we studied the association between mucin expression, inflammation and intestinal permeability in experimental colitis. Methods: We quantified 4-kDa FITC-dextran intestinal permeability and the expression of cytokines, mucins, junctional and polarity proteins at dedicated time points in the adoptive T cell transfer and dextran sodium sulfate [DSS]-induced colitis models. Mucin expression was also validated in biopsies from IBD patients. Results: In both animal models, the course of colitis was associated with increased interleukin-1β [IL-1β] and tumour necrosis factor-α [TNF-α] expression and increased Muc1 and Muc13 expression. In the T cell transfer model, a gradually increasing Muc1 expression coincided with gradually increasing 4-kDa FITC-dextran intestinal permeability and correlated with enhanced IL-1β expression. In the DSS model, Muc13 expression coincided with rapidly increased 4-kDa FITC-dextran intestinal permeability and correlated with TNF-α and Muc1 overexpression. Moreover, a significant association was observed between Muc1, Cldn1, Ocln, Par3 and aPKCζ expression in the T cell transfer model and between Muc13, Cldn1, Jam2, Tjp2, aPkcζ, Crb3 and Scrib expression in the DSS model. Additionally, MUC1 and MUC13 expression was upregulated in inflamed mucosa of IBD patients. Conclusions: Aberrantly expressed MUC1 and MUC13 might be involved in intestinal barrier dysfunction upon inflammation by affecting junctional and cell polarity proteins, indicating their potential as therapeutic targets in IBD.